New dimensions in Hindu astrology - "Mehta, S.K" (New Delhi, 2004)
This book has been written keeping in view that scientific and systematic knowledge may be provided to the students of Astrology. It presents excellent expressions of predictive Astrology which includes strength of planets in different signs, circular casting of horoscope etc.
Keywords: Astrology